Beyond Inclusion: Non-monogamies and the Borders of Citizenship - Pérez Navarro, Pablo (2016)
This paper aims to understand the extent to which monogamy operates not only as a constitutive element of marriage-like institutions but also as a metajudicial source of frequently overlooked forms of state violence. Drawing on the case of the Spanish law, it explores the privilege-driven logic that regulates the access to a complex set of economic benefits and legal protections, including immigration related rights, in order to show the extent to which monogamy is part of the grounding structure of an exclusionary constitutional citizenship. In addition, drawing on semi-structured interviews held with Spanish poly activists and biographical interviews held with LGBTQ non-monogamous people, it offers a view of non-monogamous communities as paramount spaces of resistance when it comes to re-imagining the relationship between the state and the intimate realm, beyond the mere inclusion of poly and other non-monogamous intimate relationships in certain pieces of legislation.